2012
DOI: 10.1111/j.1749-6632.2012.06827.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal pulmonary aspergillomas: case series and review

Abstract: Multifocal lung parenchymal cavities containing multiple aspergillomas are not well-recognized features of chronic pulmonary aspergillosis (CPA). We identified five patients with multiple cavities containing fungal balls from our accumulated cohort of ∼300 patients with CPA. Corticosteroid exposure and radiological and serological characteristics were assessed. The patients, aged 19-55 years, developed 3-11 cavities (or nodules in one case) with thin walls, usually within the lung parenchyma, with very limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Among the four patients who died, three of them had recurrence of aspergillosis postoperatively. One patient who had a double lung transplantation for associated cystic fibrosis died of a mycotic brain aneurysm few months following surgery, having developed ARDS after a routine surveillance bronchoscopy and lung biopsy, despite antifungal therapy [15]. The other patient who had single lung transplantation due to associated emphysema and chronic sarcoidosis died 48 months following surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Among the four patients who died, three of them had recurrence of aspergillosis postoperatively. One patient who had a double lung transplantation for associated cystic fibrosis died of a mycotic brain aneurysm few months following surgery, having developed ARDS after a routine surveillance bronchoscopy and lung biopsy, despite antifungal therapy [15]. The other patient who had single lung transplantation due to associated emphysema and chronic sarcoidosis died 48 months following surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple ‘simple aspergillomas’ without thick walls or other typical features of CNPA or CCPA can occur, but are as yet a rare finding …”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…The fungus ball may be detached from the cavity wall and imitate an air‐crescent sign . Although rare, multiple aspergillomas can occur, therefore bilateral lung involvement on chest CT does not exclude aspergilloma …”
Section: Diagnosismentioning
confidence: 99%
“…Therefore, either structural pulmonary or immunological deficiency allows this rapidly growing filamentous fungus to infect localized areas of lung. 3 Pulmonary aspergilloma usually complicates post-tuberculosis cavity. In a study, this ratio was reported as 69% of a series of 89 cases of aspergilloma.…”
Section: Discussionmentioning
confidence: 99%